ANALISIS KEBUTUHAN AIR BERSIH PERUMDA TIRTA JAM GADANG KOTA BUKITTINGGI - Tiana Gustia Nella; Surya Eka Priana; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2022)
PERUMDA Tirta Jam Gadang in the city of Bukittinggi as one of the providers of clean water is obliged to meet the clean water needs of the community by ensuring the availability of water in the long term is fulfilled. For this reason, it is necessary to analyze the current and future needs for clean water by projecting the number of residents, the number of direct connections (SL), the amount of water loss and analyzing the water discharge used by PERUMDA Tirta Jam Gadang and projecting an estimate of water availability up to 2026 with using linear regression method. Based on the results of the analysis, the total clean water needs of PERUMDA Tirta Jam Gadang until 2026 are 153.67 lt/s or an increase of 2.49% from the 2021 data which amounted to 141.59 lt/s in line with the increasing urban population growth. Bukittinggi with the number of direct connections (SL) in 2026 of 18,701 SL or an increase of 4.88% from the data in 2021 which amounted to 14,776 SL, the used water discharge of PERUMDA Tirta Jam Gadang until 2026 amounted to 240.60 lt/s or an increase of 1.85% from the used discharge data in 2021 which amounted to 233.97 lt/s, the estimated water loss until 2026 amounted to 86.23 lt/s or an increase of 2.62% from the 2021 data which is only 72.52 lt/s. With the total availability of water in 2026 which amounted to 154.37 lt/s, from the water balance it can be concluded that the availability of clean water is a surplus of 0.70 lt/s or the availability of water is still sufficient for clean water needs until 2026. Keywords: Water demand, Water availability, Water loss, Water balance, Linear  regression